An improved antiserum agar method for detecting carriage of Haemophilus influenzae type b. - Barbour, M; Crook, D; Mayon-White, RT (1993)
Enriched Columbia medium was tested against Levinthal medium for the isolation of Haemophilus influenzae type b. In both media, Haemophilus influenzae type b recovery and antigen-antibody precipitation halos were equivalent. Haemophilus influenzae type b colony size and iridescence were superior on enriched Columbia medium. Enriched Columbia medium is inexpensive, simply prepared and easily standardised.